2014
DOI: 10.1261/rna.047373.114
|View full text |Cite
|
Sign up to set email alerts
|

Subcellular transcriptome alterations in a cell culture model of spinal muscular atrophy point to widespread defects in axonal growth and presynaptic differentiation

Abstract: Neuronal function critically depends on coordinated subcellular distribution of mRNAs. Disturbed mRNA processing and axonal transport has been found in spinal muscular atrophy and could be causative for dysfunction and degeneration of motoneurons. Despite the advances made in characterizing the transport mechanisms of several axonal mRNAs, an unbiased approach to identify the axonal repertoire of mRNAs in healthy and degenerating motoneurons has been lacking. Here we used compartmentalized microfluidic chamber… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
111
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(118 citation statements)
references
References 74 publications
5
111
0
Order By: Relevance
“…SMN has been shown to localize to axons in a complex with several mRNA-binding proteins, including FMRP (Piazzon et al 2008), HuD (Fallini et al 2011), and hnRNP R (Dombert et al 2014). Additionally, compartmentalized siRNAmediated knockdown of SMN was observed to cause differential effects in the somatodendritic and axonal compartments, with the latter displaying down-regulation of genes involved in axonal growth (Saal et al 2014). Decreased SMN at axon terminals might lead to loss of important gene regulation at the synapse, and it will be interesting to see whether this impinges on early clinical changes to the motor circuitry in MNs and other cells (Mentis et al 2011).…”
Section: Spinal Muscular Atrophy (Sma)mentioning
confidence: 99%
“…SMN has been shown to localize to axons in a complex with several mRNA-binding proteins, including FMRP (Piazzon et al 2008), HuD (Fallini et al 2011), and hnRNP R (Dombert et al 2014). Additionally, compartmentalized siRNAmediated knockdown of SMN was observed to cause differential effects in the somatodendritic and axonal compartments, with the latter displaying down-regulation of genes involved in axonal growth (Saal et al 2014). Decreased SMN at axon terminals might lead to loss of important gene regulation at the synapse, and it will be interesting to see whether this impinges on early clinical changes to the motor circuitry in MNs and other cells (Mentis et al 2011).…”
Section: Spinal Muscular Atrophy (Sma)mentioning
confidence: 99%
“…Axons of sensory, cortical, hippocampal, retinal ganglion, and motor neurons have been shown to contain complex mRNA populations by RNA-seq analyses of isolated axons (18,19,(46)(47)(48)(49)(50). Despite identifying thousands of axonal mRNAs, exceptionally few RBPs have been found to date in axons.…”
Section: Discussionmentioning
confidence: 99%
“…Other RBPs implicated in axonal mRNA transport include nucleolin (Ncl), HuD (also called ELAVL4), hnRNP Q, hnRNP R, splicing factor proline and glutamine-rich (SFPQ), fragile X mental retardation (FMRP), Hermes, TRF2-S, and TDP-43 proteins (8)(9)(10)(11)(12)(13)(14)(15)(16)(17). Despite increased insight into RNA transport and translation, including the identification of literally thousands of axonal mRNAs (18,19), relatively few RBPs have been identified in axons.…”
Section: Introductionmentioning
confidence: 99%
“…The studies identified about 400 RNA species potentially binding with axonal SMN. A further study found more than 1000 genes dysregulated in neurites of NSC-34 cells and smn-depleted primary mouse motor neurones [121][122][123]. Among these genes are a number involved in axonal outgrowth, synaptogenesis, neurogenesis and neurotransmitter release [121,122].…”
Section: Accepted Manuscriptmentioning
confidence: 97%